PhoneProtector: Protecting User Privacy on the Android-Based Mobile Platform - Weizhe Zhang; Hui He; Qizhen Zhang; Tai-hoon Kim (International Journal of Distributed Sensor Networks)
With the popularity of Android platform based mobile phones, privacy protection of Android platform becomes a focus area. Now protection for Android based smart phone has many shortages, and also most phone protection systems are based on C/S model. In this paper, we propose a browser-free multilevel smart phone privacy protection system, which is based on the Android sensor platform. In this system, protection is ensured by means of SMS, which turns out to be easy, quick, and convenient. Users can send SMS to phones remotely as operating instructions; then the sensors on remote phones execute the instructions and return useful information. Second, the sensors based on the daemon process mechanism are used to prevent the sensors from being maliciously closed and uninstalled. Third, our system adopts SIM detecting mechanism to judge whether the SIM card is removed or changed. If exception is detected, the phone will be locked automatically by its inside sensors. The three points ensure full protection of phone privacy. Test results show that our system has good robustness and low resource consumption.